Comparison of clinical validation of acceleromyography and electromyography in children who were administered rocuronium during general anesthesia: a prospective double-blinded randomized study - Jung, Woojun (Korean J Anesthesiol, 2016)
BACKGROUND: Electromyography and acceleromyography are common neuromuscular monitoring devices. However, questions still remain regarding the use of acceleromyography in children. This study compared the calibration success rates and intubation conditions in children after obtaining the maximal blockade depending on each of the devices METHODS: Children, 3 to 6 years old, were randomly allocated to the TOF-Watch SX acceleromyography group or the NMT electromyography group. The induction was performed with propofol, fentanyl, and rocuronium. The bispectral index and 1 Hz single twitch were monitored during observation. The calibration of the each device was begun when the BIS dropped to 60. After successful calibration, rocuronium 0.6 mg/kg was injected. A tracheal intubation was performed when the twitch height suppressed to 0. The rocuronium onset time (time from administration to the maximal depression of twitch height) and intubating conditions were rated in a blinded manner. RESULTS: There was no difference in the calibration success rates between the two groups; and the calibration time in the electromyography group (16.7 ± 11.0 seconds) was shorter than the acceleromyography group (28.1 ± 13.4 seconds, P = 0.012). The rocuronium onset time of the electromyography group (73.6 ± 18.9 seconds) was longer than the acceleromyography group (63.9 ± 18.8 seconds, P = 0.042) and the intubation condition of the electromyography group (2.27 ± 0.65) was better than the acceleromyography group (1.86 ± 0.50, P = 0.007). CONCLUSIONS: Electromyography offers a better compromise than acceleromyography with respect to the duration of calibration process and surrogate for the optimal time of tracheal intubation in children.